Designing a compact MRI motion phantom - Schmiedel Max; Moeller Anita; Koch Martin A.; Mertins Alfred (Current Directions in Biomedical Engineering, 2016)
Even today, dealing with motion artifacts in magnetic resonance imaging (MRI) is a challenging task. Image corruption due to spontaneous body motion complicates diagnosis. In this work, an MRI phantom for rigid motion is presented. It is used to generate motion-corrupted data, which can serve for evaluation of blind motion compensation algorithms. In contrast to commercially available MRI motion phantoms, the presented setup works on small animal MRI systems. Furthermore, retrospective gating is performed on the data, which can be used as a reference for novel motion compensation approaches. The motion of the signal source can be reconstructed using motor trigger signals and be utilized as the ground truth for motion estimation. The proposed setup results in motion corrected images. Moreover, the importance of preprocessing the MRI raw data, e.g. phase-drift correction, is demonstrated. The gained knowledge can be used to design an MRI phantom for elastic motion.